Rewriting logic and its applications : 12th International Workshop, WRLA 2018, held as a satellite event of ETAPS, Thessaloniki, Greece, June 14-15, 2018, Proceedings /: 12th International Workshop, WRLA 2018, held as a satellite event of ETAPS, Thessaloniki, Greece, June 14-15, 2018, Proceedings. (2018) - Unknown
No abstract available